Efficacy and safety of CT-guided 125I particle implantation for the treatment of elderly lung cancer: a system evaluation and meta-analysis - Qiuping Li; Yingrui Huang; Chuncheng Shen; Jiatong Zhou; Ping Lin; Yanfei Lu; Anxin He; Xiang Liu; Miao Luo (BMC Geriatrics)
Abstract Background To systematically evaluate the efficacy and safety of 125I particle implantation in the treatment of elderly lung cancer. Methods Both randomized and non-randomized controlled studies on CT-guided 125I particle implantation therapy for the treatment of elderly lung cancer patients were retrieved from databases including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, Wanfang Data, VIP, and SinoMed from inception to October 31, 2022. Two researchers screened the retrieved studies, extracted data, and evaluated the study quality independently. Then, meta-analysis was conducted using RevMan5.3 and Stata15 software. Results A total of 15 studies were included, involving 886 subjects. The meta-analysis results showed that compared with the control group, the 125I particle implantation group had a higher objective response rate [RR = 1.71, 95% CI 1.50–1.96, P < 0.001] and disease control rate [RR = 1.30, 95% CI 1.19–1.43, P < 0.0001], longer survival [HR = 0.48, 95% CI 0.37–0.63, P = 0.0005], but an 8.96-fold increase in postoperative complications [RR = 8.96, 95% CI 4.75–16.92, P < 0.0001]. There was no significant difference in the incidence of adverse reactions between the two groups [RR = 1.02, 95% CI 0.91–1.14, P = 0.73]. Conclusions The CT-guided 125I particle implantation therapy is able to significantly improve the short-term efficacy and survival of elderly patients with lung cancer. Although the risk of complications was significantly increased, none of the included studies reported serious complications. Our meta-analysis exhibited clinical heterogeneity due to non-uniform interventions, varied treatment protocols, inconsistent staging criteria, and study limitations such as small samples, few studies and short follow-up, potentially introducing bias. More high-quality research is needed to further validate the conclusions of this study. Clinical trial number This study has been registered on the PROSPERO platform (Registration number: CRD420251078821).